Synthesis of novel N-substituted β-amino acid derivatives bearing 2-hydroxyphenyl moieties as promising antimicrobial candidates targeting multidrug-resistant Gram-positive pathogens - Povilas Kavaliauskas; Birutė Grybaitė; Birute Sapijanskaite-Banevič; Rūta Petraitienė; Ramunė Grigalevičiūtė; Andrew Garcia; Ethan Naing; Vytautas Mickevičius; Sergey Belyakov; Vidmantas Petraitis (PLoS ONE, 2025)
The increasing prevalence of antimicrobial resistance among ESKAPE group pathogens presents a significant challenge in the healthcare sector, contributing to higher morbidity and mortality rates globally. Thus, it is essential to develop novel antimicrobial agents effective against drug-resistant pathogens. In this study, we report the synthesis and in vitro antimicrobial activity characterization of novel N-substituted β-amino acid derivatives bearing 2-hydroxyphenyl core against multidrug-resistant bacterial pathogens. The synthesized compounds (2–26) exhibited promising antimicrobial activity specifically against Gram-positive bacteria, with minimum inhibitory concentrations (MIC) ranging from 4 to 128 µg/mL. Compounds 9 (R = 4-nitrophenyl), 17 (R = 5-nitro-2-thienyl), 18 (R = 5-nitro-2-furyl), thiosemicarbazide 16, and 26 exhibited the most promising activity against Staphylococcus aureus MRSA USA300 lineage strain TCH-1516, with MIC values between 4 and 16 µg/mL. Compound 26 demonstrated strong antimicrobial activity against both S. aureus TCH-1516 and E. faecalis AR-0781, with the activity comparable to control antibiotics. Furthermore, compound 26 exhibited antifungal activity drug-resistant against Candida albicans AR-0761 (MIC 16 µg/mL). These findings indicate that N-substituted β-amino acid derivatives with a 2-hydroxyphenyl core warrant further investigation as a potential scaffold for the further development of antimicrobial agents based on compound 26 targeting Gram-positive pathogens and drug-resistant C. albicans AR-0761.